1967
DOI: 10.1126/science.157.3794.1327
|View full text |Cite
|
Sign up to set email alerts
|

Globin Composition and Synthesis of Hemoglobins in Developing Fetal Mice Erythroid Cells

Abstract: Fetal mouse erythropoiesis proceeds initially in yolk-sac blood islands (8 to 12 days) and, subsequently, in liver (12 to at least 16 days). Yolksac cells synthesize three hemoglobins, Hb E(I), Hb E(II) and Hb E(III). Hb E(I) has x- and y-globin chains; Hb E(II) has alpha and y; HB E(III), alpha and z. No detectable beta-globin is formed in these cells. Liver erythroid cells form only adult hemoglobin, composed of alpha- and beta-chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
59
0
1

Year Published

1970
1970
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(64 citation statements)
references
References 14 publications
4
59
0
1
Order By: Relevance
“…2 indicated that during the early developmental stage there was a switch of the subcellular localization of EKLF in the erythroid cells from the cytosol to the nucleus. This switch coincided with the timing of the switch-on of ␤ maj globin gene transcription (13,26,38,54,57). The nuclear localization of EKLF in the E10.5 yolk sac and E14.5 fetal liver tissues (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2 indicated that during the early developmental stage there was a switch of the subcellular localization of EKLF in the erythroid cells from the cytosol to the nucleus. This switch coincided with the timing of the switch-on of ␤ maj globin gene transcription (13,26,38,54,57). The nuclear localization of EKLF in the E10.5 yolk sac and E14.5 fetal liver tissues (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the adult mouse fi-globin genes, the mouse a-globin genes are expressed during both fetal and adult life (24). In addition, the mature form of the a-globin mRNA appears to be synthesized via a small 850-base precursor, approximately 250 bases larger than the cytoplasmic a-globin mRNA (25,26).…”
mentioning
confidence: 99%
“…In the mammalian adult, erythropoietin is a they persist until about day 17 (Craig and Russell, major factor regulating the rate of erythropoiesis 1964 ; Fantoni et al ., 1967) . By the latter part of in response to physiological demand (Gurney, day 10 of gestation, hepatic erythropoiesis begins 1968) .…”
Section: Introductionmentioning
confidence: 99%